Rapid and sustained effects of a single dose of benralizumab on chronic eosinophilic pneumonia. (2020) - Izumo, Takehiro; Kuse, Naoyuki; Awano, Nobuyasu; Tone, Mari; Jo, Tatsunori; Yoshimura, Hanako; Minami, Jonsu; Takada, Kohei; Muto, Yutaka; Fujimoto, Kazushi; Inomata, Minoru
Abstract: Chronic eosinophilic pneumonia (CEP) is an eosinophilic inflammatory disease of unknown etiology, and oral corticosteroid (OCS) is commonly used for its treatment. Approximately half of CEP cases relapse secondary to reduction or termination of OCS. A 43-year-old woman visited our hospital because of a chronic cough and abnormal chest X-ray findings. She was diagnosed with CEP because of marked eosinophilia, as well as eosinophilic infiltrates in cryobiopsy samples. After initiation of OCS treatment, her symptoms disappeared with a decrease in peripheral blood eosinophil counts and the amelioration of abnormal infiltrative shadows on chest X-ray. However, symptoms reappeared after OCS termination, including a recurrence of eosinophilia and appearance of fresh abnormal shadows on chest X-ray. Because she refused readministration of OCS because of side effects such as appetite enhancement and moon face in last treatment course, we administered her a single dose of benralizumab. Her symptoms and peripheral eosinophil counts were markedly ameliorated 1 week after benralizumab administration. The marked amelioration in abnormal shadows on chest X-ray were maintained 2 weeks after benralizumab administration. She had no relapse of CEP for almost 6 months after benralizumab administration. Our experience with this case suggests that a single dose of benralizumab may be a treatment option for relapsed CEP cases or those with side effects of long-term OCS therapy.